Pengaruh Pengendalian Intern, Komitmen Organisasi Dan Kompetensi Sumber Daya Manusia Terhadap Sistem Informasi Akuntansi Pada CV. Merapi Kendal Jawa Tengah - Susi Nurma Septiani; Bagus Kusuma Ardi (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2021)
The purpose of this study was to determine the Accounting Information System for Cash Receipts in CV. Merapi Kendal, Central Java. The type of research that will be used is associative with a quantitative approach. The population in this study were employees of CV. Merapi Kendal, Central Java, which found 183 people, while the sample used in this study was 40 respondents using purposive sampling technique. The method of data collection through the distribution of the analysis questionnaire used in this study was multiple linear regression The results showed that Internal Control, Human Resource Competence and Organizational Commitment had a positive and significant effect on Accounting Information Systems and the adjusted value of R square in the regression model obtained was 0.816, which means that 81.6 percent of Accounting Information System variables can be explained by the variable Internal Control, Human Resource Competence and Organizational Commitment while the remaining 18.4 percent is explained by other variables outside this study.